Ultra Petita Decision of Constitutional Court on Judicial Review (The Perspective of Progressive Law) - Sasmito, Hery Abduh (Faculty of Law, Universitas Negeri Semarang, 2016)
This research come up from the premise that in the execution of their duties during this time, the Constitutional Court issued many decisions by some legal experts considered break the limits of his authority. One is on a judicial review which contains ultra petita decisions. Regarding to that condition, some parties considered that the Court has acted as an institution that is authoritarian and violated its authority, but on the other hand, the Court instead declared itself as the guardian of democracy and substantive justice. Author argued that, the prohibition to use a doctrine of ultra petita for judge was not generally applicable. Through normative approach and systematic interpretation said that on Law concerning to Constitutional Court (MK, Mahkamah Konstitusi) or other MK decisions did not give any possibilities for Judge to make an ultra petita decision.